Panopticon sebagai Konsepsi Pengawasan dalam Perancangan Arsitektural - Muhammad Rakhan Agil; Johannes Adiyanto (Archvisual: Jurnal Arsitektur dan Perencanaan, 2025)
Creating a comprehensive security architecture that covers both technological and organizational aspects of BIM security. Digital surveillance has become an inherent aspect of modern life, with technology such as big data, algorithms, and artificial intelligence monitoring and collecting individual personal data from architects' creative work processes. This paper discusses how the concept of the panopticon, which was originally designed for a social institution and later interpreted by Michel Foucault and Deleuze, is relevant to understanding how power operates through concealed but ongoing observation. The panopticon was initially a prison architecture in which convicts felt continually observed even when the supervisor was not present. In the digital era in all areas, this study focuses on architectural design.